Cutting edges in Clostridioides difficile infections (Swiss Medical Weekly, 2021)
Clostridioides difficile is the most common cause of hospital-acquired diarrhoea and one of the most important causes of hospital-acquired infections. It results in significant morbidity, mortality and economic burden - especially in the context of recurrent infections. After initial antibiotic therapy of a C. difficile infection, recurrence occurs in about 20% of all patients, which increases the risk of further recurrence to about 45%.Traditional therapeutic options for treatment of C. difficile infection include metronidazole or vancomycin. Newer therapy options such as fidaxomicin, the administration of monoclonal antibodies or faecal microbiota transplantation demonstrate significant advantages over traditional therapies, particularly regarding the reduction of the recurrence rate.This article highlights the main differences between the recommendations of the Swiss Society for Infectious Diseases on the management of “Clostridioides difficile infection” and the IDSA/SHEA reference guideline “Clinical Practice Guidelines for Clostridium difficile Infection in Adults and Children: 2017 Update by the Infectious Diseases Society of America (IDSA) and Society for Healthcare Epidemiology of America (SHEA)” and discusses some important challenges in -treatment of C. difficile.